Childhood and ethical inquiries: from the transitional present to the dictatorial past in Lina Meruane’s "Señales de nosotros" - Contreras Candia, Leticia (Árboles y Rizomas, 2023)
In commemoration of the 50th anniversary of the civic-military coup and the unsettling denial promoted by various sectors of the society who aim to turn the page and look towards the future, this article argues for the need to interpret Lina Meruane's Señales de nosotros (2023) from two lines of analysis. On one hand, to comprehend that the fictional exercise crafted by Meruane critically explores the representations of the dictatorial past from an enunciative present linked to the symbolic-cultural framework of the transition. On the other hand, Señales de nosotros problematizes children and teenagers who lived during the dictatorship, ruled by normative production conditions and political violence. We aim to analytically trace the textual clues or signals that allow us to substantiate our reading hypotheses through three image-codes: a self-fictionalized memory, family constellations, and pedagogical-cultural imaginaries.
Keywords: literature of the children; self-fiction; dictatorship; ethics; transition